THE EFFECT OF NEEDS AND GLOBALIZATION ON INTEREST OF TEENAGERS IN TRADITIONAL ARTS - Neni Purnamasari; Irawan Suntoro; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2012)
This research was aimed to explain and examine the effect of the need for teenagers interest in traditional arts performances in the patoman village of pagelaran sub district in Pringsewu regency, to explain and examine the effect of globalization on teenagers interest in traditional arts performances in the patoman village of pagelaran sub district in Pringsewu regency.This research used descriptive correlational method with 48 respondents as the sample. The basic techniques of data collecting used questionnaires, interview and observation. Data analysis using Chi quadratic.Based on testing and data analysis can be known that: 1. There are significant needs for teenagers interest in the traditional arts performances in the Patoman village of Pagelaran sub district in Pringsewu regency in 2013. This means that interest teens in the traditional arts is determined by the needs of the desire, the will and expectations of young people in the arts tradisional.Key Word : globalization, interests, teenagers, arts, traditional